Analisis Pendapatan dan Kelayakan Usahatani Padi Sawah Pasang Surut di Desa Cemara Labat Kecamatan Kapuas Kuala Kabupaten Kapuas - Rajudinnor Rajudinnor (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
Agricultural development is basically one of the systems development is no less important in supporting the success of the national development. Development of the agricultural sector aims to develop agricultural businesses in rural areas that will spur rural economic activity, create jobs and improve the welfare of society grow upstream, downstream and support in enhancing the competitiveness and added value of agricultural products. The purpose of this study to: (i) large knowing rice farming income in Cemara Labat Village Kapuas Kuala District Kapuas regency, (ii) determine the feasibility of rice farming In Cemara Labat Village Kapuas Kuala District Kapuas regency. Determination of respondent committed intentionally (purposive), Total farmer respondents (sample) taken in this study of 30 rice farmers. The analysis used in this research is revenue analysis and feasibility analysis. The results showed that rice farming income in the village of Cemara Labat Kapuas Kuala District of Rp 10.807.462 Ha-1. Rice farm In Cemara Labat Village Kapuas Kuala District Kapuas regency viable with the value of revenue cost ratio (RCR ) to 2.73, which means that any expenditure of Rp 1.000,- will generate revenue of Rp 2.730,-.